Fuzzy sliding-mode control of structures - Alli, H; Yakut, O (Elsevier Sci Ltd, 2005)
In this study, fuzzy sliding-mode control (FSMC) method, which is one of the active control algorithms, has been applied for seismic isolation of earthquake-excited structures. The chattering effect, the major disadvantage of conventional sliding-mode controller. has been removed by introducing FSMC without losing the robustness against parametric uncertainties. modeling inaccuracies and varying dynamic loads. For numerical applications. an eight-storey shear building excited by earthquake loads has been considered. The around accelerations recorded in two different earthquake events, which are the east-west acceleration components of Duzce and Bolu records of 1999 Duzce-Bolu earthquake, in Turkey, have been used to evaluate the effectiveness of the control algorithm for varied disturbances. Finally the simulation results have been presented in graphical form and the effectiveness of the proposed controller has been compared with that of the conventional sliding-mode controller. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: fuzzy; sliding-mode; control; chattering; seismic isolation; structures